مشكلة التخلص من المواليد الجدد بين الفقه الإسلامي والقانون الماليزي : دراسة حالة في ولاية كلنتان - Nik Nor Azeah Nik Azman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research aims to study the problem of baby dumping in Malaysia, especially in Kelantan, the solutions in the perspective of Islamic jurisprudence and Malaysian law. This research deals with the statistical problem of disposing of birth sin Malaysia, and the basic statement of there a sons for the spread of this problem; the statement of the government's role in the solution of this problem, and the solutions for solving this cases from the perspective of Islamic law and Malaysian, through government solutions, and non-government organizations, family and individually. The researcher adopted inductive methodology to gather all the information about the concept, and the evidence, and the status and the rights of children in Islamic law and others related topic, As well as an analytical approach in the presentation of information on the causes and solutions to this problem. The way to get the information by publish questions among the community and meet some government departments that have a role in addressing the problem of baby dumping in Malaysia, and a special Kelantan term. In summary, one of the most important results is that the problem of baby dumping in Kelantan is a big problem that must be completed by, because based on statistical records made the Royal Malaysian Police to get rid of birth of more than a year. The ways to address the problem of baby dumping of solutions birth comes not only from the government, and non-governmental organizations, community, and family, but every society of Malaysia has role in preventing the problem of baby dumping in this country.